PENGEMBANGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF - Sutinah - Sutinah; Nurhadji - Nugraha; Sudarmiani - Sudarmiani (STKIP PGRI TULUNGAGUNG, 2022)
This study aims to determine whether developing an audio-visual assisted problem-based learning (PBL) learning model can improve the cognitive learning outcomes of 5th grade students of SDN 03 Klegen Madiun.This study uses a Research and Development (RD) research and development method. The Research and Development method (RD is research used to produce certain products and test the effectiveness of these products (Sugiyono 2015). The development model that researchers will use is the ADDIE (Analysis-Design-Development-Implementation-Evaluation) model. Cheung (2016) states that ADDIE is a model that is easy to use and can be applied in curricula that teach knowledge, skills or attitudes.The results of the research after going through expert validation and limited trials, then carried out extensive trials with the results: (a) the learning aspect obtained an average score of 77.14, with good criteria; (b) the display aspect obtained an average score of 79.74, with good criteria; and (c) aspects of the content of the material get an average of 81.46, with very good criteria. Furthermore, based on the broad trial assessment, there were 6 students or 18.75% of the incomplete results (score Minimum Completeness Criteria), while students who completed learning were 26 people or 81.25% (score acquisition Completeness Criteria. Minimum).